A response to "Assessing the impact of transdisciplinary research: The usefulness of relevance, credibility, and legitimacy for understanding the link between process and impact". Issue 2 (15th December 2018) - Belcher, Brian M; Ramirez, Luisa F; Davel, Rachel; Claus, Rachel
Abstract: Hansson and Polk (2018, Research Evaluation, 27/2: 132–44) aim to assess the usefulness of the concepts of relevance, credibility, and legitimacy for understanding the link between process and impact in transdisciplinary (TD) research. However, the article misrepresents some of the ideas in the two main reference articles. It also uses definitions of the concepts it aims to test that are inconsistent with the definitions offered by the reference papers. The methods description is insufficient to know what data were collected or how they were analyzed. More importantly, the effort to understand relationships between process and impact in TD research needs more careful definitions of the concepts outcome and impact as well as more objective ways to assess outcomes and impacts. This letter discusses shortcomings in the article and makes suggestions to improve conceptual clarity and methods for empirically assessing TD research effectiveness.